DETERMINANT PRINCIPLES OF FORMATION PROFESSIONAL MOTIVATION OF A LAWYER: ADMINISTRATIVE AND LEGAL CHARACTERISTICS - Blikhar, Mariia (Socio-economic relations in the digital society, 2025)
The article examines, within the framework of administrative and legal discourse, the determinants of the formation of a lawyer’s professional motivation. It is found that the characterization of a lawyer’s professional motivation covers a wide range of factors which influence the desires and needs of future legal professionals. One of the key elements is the motivational core of legal education students. It is also substantiated that the motivation for obtaining a legal profession may vary, since some young people may see their future profession as a source of material well-being, while for others, the priority is the opportunity to “find” themselves in a certain type of legal activity, and, having decided on the future specialization, to embark on the path of professional development and career growth. That is why, already during their studies, the vast majority of applicants seek to find and further expand the scope of practical skills necessary for future work in the legal industry. The analysis shows that the gradual introduction of professionally oriented training into the system of higher legal education in Ukraine creates opportunities to overcome this discrepancy by modelling the elements of professional activity of future lawyers during the educational process. In particular, innovative methods of organizing and conducting moot courts, various types of business games, interactive learning, participation in legal clinics, etc. are effective. Moreover, future lawyers try their hand at public debates, learn to defend clients’ interests in courts and gain negotiation skills. As mediators, they become involved in dispute resolution, counselling, conducting interviews, empirical research, etc. Such training gives a good result, and under the guidance of a research and teaching staff member of a higher education institution, it creates new opportunities for more active use of the knowledge gained, while showing the depth of its assimilation and the level of development of creative thinking. In interaction with the teacher, the higher education student learns to build business relationships, understand the requirements of professional ethics, the essence of the corporate culture of a lawyer, etc.